Correlation between Chest X-Rays and TCM (Rapid Molecular Tests) in Pulmonary Tuberculosis Patients at Anutapura Hospital Palu - Ria Sulistiana (Sean Institute, 2023)
Tuberculosis (TB) is an infectious disease that can cause a decline in health, caused by Mycobacterium tuberculosis. The Molecular Rapid Test with Xpert MTB/RIF is a test tool using a cartridge based on the Nucleic Acid Amplification Test (NAAT) to identify Mycobacterium tuberculosis and resistance to rifapicin. Radiology plays an important role in diagnosis and evaluation of TB cases. Thoracic X-ray is required if the patient with a negative Molecular Rapid Test result but has strong clinical manifestations. Method: This research is an observational analytic study with a cross sectional approach. The sampling technique used is total sampling also using secondary data. The amount of sample is 154 patients. The statistical test used is the Spearman test and the Lambda. Contingency Coefficient test. Result: The results showed, there is 15 (9,7%) in MTB not detection, 58 patients (37,7%) in MTB detected low, 62 (40,3%) in MTB detected medium, and 19 (12,3%) MTB detected high. Minimal lesion is 14 (9,1%) and advanced lesion 140 (90,9%). Typical lesion location 142 (92,2%) and atypical location 12 (7,8%). There is a significant relationship between the area of the lesion on the chest radiograph and the Molecular Rapid Test examination with a p value of 0.000 (p value < 0.05) and a correlation coefficient value of r = 0.527, and there is no significant relationship between the location of the lesion on a chest X-ray with a Rapid Molecular Test examination with a p value of 0.615. Conclusion: There is a significant and strong relationship between lesion area in chest x-ray and Molecular Rapid Test results. And there is no relationship between the location of the lesion on the chest X-ray with Molecular Rapid Test results.